Glycolysis is intrinsically required in the follicle stem cell lineage but not in female germline stem cells or their early progeny in Drosophila melanogaster. - Wessel, E.M.; Drummond-Barbosa, D. (Genetics, 2026)
Multiple tissue stem cells depend on glycolysis or ?-oxidation for cell fate decisions. However, how universal these requirements are and how they change as stem cell daughters undergo differentiation remains unclear. The Drosophila ovary is a powerful stem cell model with two distinct stem cell populations: germline stem cells (GSCs), which produce oocytes to perpetuate the species, and follicle stem cells (FSCs), a somatic lineage. Several studies have begun addressing the roles of metabolism within the Drosophila female GSC lineage, but direct systematic analyses of glycolysis and/or mitochondrial fatty acid ?-oxidation requirements across these lineages have been lacking. Here, using genetic mosaic analysis with null alleles, we found that genes encoding key regulatory glycolytic enzymes-Phosphofructokinase (Pfk) and Pyruvate kinase (Pyk)-are not cell autonomously required for GSC maintenance, proliferation, or early differentiation through 16-cell germline cyst formation and oocyte specification. Although germline cysts lacking Pfk or Pyk function can develop through early vitellogenesis, they grow slowly and display impaired nurse cell chromatin dispersal. By contrast, FSCs and their early daughters require Pfk (but not Pyk) for normal survival, while later follicle cells need both Pfk and Pyk for survival and only Pfk for proliferation, suggesting that follicle cells predominantly require glycolytic intermediates upstream of Pyk. Surprisingly, mitochondrial ?-oxidation was dispensable in both lineages. These findings uncover an unusual metabolic state in GSCs and their early daughters, with marked differences from the neighboring FSC lineage and other somatic stem cells.